2013
DOI: 10.1681/asn.2013010019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Urinary Biomarker Panel for Incident Kidney Disease and Clinical Outcomes

Abstract: Whether novel biomarkers improve the assessment of incident kidney disease and related adverse outcomes remains to be tested in longitudinal observational studies. We tested 14 urinary biomarkers for association with incident kidney, cardiovascular, and mortality outcomes in 2948 Framingham Heart Study participants. Baseline examinations were performed between 1995 and 1998; mean follow-up was 10.1 years for renal outcomes and 11.2 years for survival analyses. Primary outcomes were incident CKD, incident album… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 50 publications
(46 reference statements)
3
40
1
1
Order By: Relevance
“…Moreover, we recently reported that higher urinary KIM-1 is associated with an increased risk for incident heart failure hospitalizations in the community-based ULSAM cohort (19). Our findings of an association between urinary KIM-1 and total mortality is in accordance with two recent community-based studies (27,28); however, in one of these, no association between KIM-1 and cardiovascular mortality was found (28). Perhaps differences in the protocol for urine collection (spot sample versus 24-hour collection), or differences in age and gender distribution of the study samples may explain the discrepancy between the previous study and the present study.…”
Section: Comparison With the Literaturesupporting
confidence: 91%
“…Moreover, we recently reported that higher urinary KIM-1 is associated with an increased risk for incident heart failure hospitalizations in the community-based ULSAM cohort (19). Our findings of an association between urinary KIM-1 and total mortality is in accordance with two recent community-based studies (27,28); however, in one of these, no association between KIM-1 and cardiovascular mortality was found (28). Perhaps differences in the protocol for urine collection (spot sample versus 24-hour collection), or differences in age and gender distribution of the study samples may explain the discrepancy between the previous study and the present study.…”
Section: Comparison With the Literaturesupporting
confidence: 91%
“…The relationship between urinary uromodulin excretion and glomerular filtration has long been debated, with some studies showing positive associations (11,12) and others not (33). Our data demonstrate a linear, positive association between uromodulin and eGFR, but only when eGFR is ,90 ml/min per 1.73 m 2 .…”
Section: Discussionsupporting
confidence: 41%
“…Wu et al (32) additionally showed that individuals with drug-induced interstitial nephritis had higher levels of urine a1m compared with age-and sex-matched controls and that urine a1m levels correlated with the degree of inflammatory infiltration, interstitial edema, and tubular atrophy on kidney biopsy. Finally, O'Seaghdha et al (33) investigated the associations of multiple urinary biomarkers, including a1m, with incident kidney disease and related outcomes in 2948 Framingham Heart Study participants. Although urine a1m was not associated with incident CKD or albuminuria, each 1 SD of log-transformed a1m was associated with a 30% higher risk for all-cause mortality (33).…”
Section: Discussionmentioning
confidence: 99%